Gender differences in response to warrelated trauma and posttraumatic stress disorder – a study among the Congolese refugees in Uganda - Ainamani, Herbert E.; Elbert, Thomas; Kani Olema, David; Hecker, Tobias (BMC psychiatry, 2020)
The wars in the Democratic Republic of Congo have left indelible marks on the mental health and functioning of the Congolese civilians that sought refuge in Uganda. Even though it is clear that civilians who are exposed to potentially traumatizing events in war and conflict areas develop trauma-related mental health problems, scholarly information on gender differences on exposure to different war-related traumatic events, their conditional risks to developing PTSD and whether the cumulative exposure to traumatic events affects men and women differently is still scanty. Methods: In total, 325 (n=143males, n = 182 females) Congolese refugees who lived in Nakivale, a refugee settlement in the Southwestern part of Uganda were interviewed within a year after their arrival. Assessment included exposure to war-related traumatic events, and DSM-IV PTSD symptom severity. Results: Our main findings were that refugees were highly exposed to war-related traumatic events with experiencing dangerous flight as the most common event for both men (97%) and women (97%). The overall high prevalence of PTSD differed among women (94%) and men (84%). The highest conditional prevalence of PTSD in women was associated with experiencing rape. The dose-response effect differed significantly between men and women with women showing higher PTSD symptom severity when experiencing low and moderate levels of potentially traumatizing event types. Conclusion: In conflict areas, civilians are highly exposed to different types of war-related traumatic events that expose them to high levels of PTSD symptoms, particularly women. Interventions focused at reducing mental health problems resulting from war should take the context of gender into consideration.
Keywords: Refugees; Gender; War; Trauma; Posttraumatic stress disorder (PTSD)